2018
DOI: 10.3390/ijfs6030064
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Exchange Traded Funds during the Brexit Referendum: An Event Study

Abstract: In today's interrelated economies, financial information travel at speed of light to reach investors around the globe. Global financial markets experience regular shocks that transmit negative waves to other equity markets and different asset classes. Given the unique characteristics of exchange-traded funds (ETFs), this paper examines how different ETFs that are traded on London Financial center reacted to the Brexit event in 23 June 2016. The unexpected referendum result the day after is viewed as the next s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In the event study methodology, there is no universal rule on the lengths of the event windows. Over the years, many articles used the event study methodology and changed the size of the event window according to the research needs [20][21][22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…In the event study methodology, there is no universal rule on the lengths of the event windows. Over the years, many articles used the event study methodology and changed the size of the event window according to the research needs [20][21][22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…The Performance of exchange-traded funds during the Brexit has been analysed by Alkhatib and Harasheh (2018). The study shows that the world equity's ETFs significantly respond to the event by having a significant positive abnormal return K on the event date.…”
Section: State Of Research-event Studies In the Context Of Brexitmentioning
confidence: 99%
“…Authors modeled ARMA 3 models of the volatility indices with the inclusion of fractal integration in the observed processes and found that in the short run the Brexit vote had a significant impact on all series except the exchange rate to Yen. Alkhatib and Harasheh (2018) apply the ESM approach to the exchange traded funds (ETFs) on London Financial Centre with the event window of −10 to +10 days. The funds have been grouped into several clusters, depending upon the region the ETFs were investing the most (e.g., emerging markets).…”
Section: Previous Related Researchmentioning
confidence: 99%